Anonymity versus advocacy: challenges and pitfalls of ethical island research. Issue 6 (1st November 2020) - Matheson, Kate; Pawson, Chris; Clegg, Peter
ABSTRACT: The purpose of much island research is to advocate for island communities, to encourage island scholarship by islanders themselves, and where that is not possible, to promote the voices of islanders 'on their own terms'. However, the very nature of small islands as socially and physically bounded communities, means that, whilst one voice cannot speak for the entire community, often the voice speaking is easily recognisable. This can result in the risk of local retribution, or more commonly truths going unspoken and power imbalances remaining unaddressed. To undertake island scholarship, it may be necessary in some cases, to anonymise the island, or at least aspects of it, in order to anonymise the speaker. In this paper, by drawing on examples from our own research on islands around the UK and other research in very small island communities, we consider the difficulty participants may face in speaking openly, and address the conflicts that confront researchers between supporting island stories whilst also offering a balanced reflection of island life. We suggest that while it is clearly important that island voices are heard, and that islanders speak on their own terms, there are instances where the off-island voice may be better placed to address island issues. The best route to do this may be via some form of anonymisation of subject and/or place of the research.